2021
DOI: 10.3389/fpsyt.2021.584416
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxin Therapy for Depression: Therapeutic Mechanisms and Future Perspective

Abstract: Depression is one of the most common mental disorders, which causes global burden. Antidepressants and psychotherapies are the mainstay of treatment for depression, which have limited efficacy. Thus, alternative approaches for preventing and treating depression are urgently required. Recent clinical trials and preclinical researches have clarified that peripheral facial injection of botulinum neurotoxin type A (BoNT/A) is a rapid, effective and relative safe therapy for improving some symptoms of depression. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 84 publications
0
10
0
8
Order By: Relevance
“…The effect of BoNT/A was associated with an enhancement of 5-HT level and the expression of brain derived neurotrophic factor in hippocampus, hypothalamus, prefrontal cortex, and amygdala, together with the transiently increased levels of p-ERK and CREB. These preclinical studies, together with some indirect clinical evidence [114,115], suggest BoNT/A as alternative treatment for depression. However, the direct injection of BoNTs to the brain is a procedure that poses ethical and practical difficulties to translate therapeutical benefit from animal model to human.…”
Section: Central Effects Of Bonts After Direct Injection On Cnsmentioning
confidence: 92%
“…The effect of BoNT/A was associated with an enhancement of 5-HT level and the expression of brain derived neurotrophic factor in hippocampus, hypothalamus, prefrontal cortex, and amygdala, together with the transiently increased levels of p-ERK and CREB. These preclinical studies, together with some indirect clinical evidence [114,115], suggest BoNT/A as alternative treatment for depression. However, the direct injection of BoNTs to the brain is a procedure that poses ethical and practical difficulties to translate therapeutical benefit from animal model to human.…”
Section: Central Effects Of Bonts After Direct Injection On Cnsmentioning
confidence: 92%
“…However, the cumulating evidence of the efficacy of BoNT in such indications is not per se evidence of the accuracy of this rationale. Our previous study, which showed an antidepressant effect of BoNT across a broad range of indications and injection sites, opened up a broad spectrum of possible explanations for this effect 8 , 40 . Some of theses explanations are compatible with the facial feedback hypothesis while others challenge it.…”
Section: Discussionmentioning
confidence: 96%
“…The evaluation of well-being promoted by BT-A application goes beyond the aesthetic benefits. The potential therapeutic in the emotional states shown in several clinical studies toward the new use of BT-A, mainly in patients who do not respond to antidepressant medications [ 29 , 30 ]. It is important to consider that different symptoms and depression grades can contribute to heterogeneity of the improvement of depression statements, and it is not clear if the severity of the mood state requires higher BT-A dosages (units/muscle).…”
Section: Discussionmentioning
confidence: 99%